Postsynaptic Density Protein 95 in the Striosome and Matrix Compartments of the Human Neostriatum - Morigaki, Ryoma; Goto, Satoshi (Frontiers in Neuroanatomy, 2015)
The human neostriatum consists of two functional subdivisions referred to as the striosome (patch) and matrix compartments. The striosome-matrix dopamine systems play a central role in cortico-thalamo-basal ganglia circuits, and their involvement is thought to underlie the genesis of multiple movement and behavioral disorders, and of drug addiction. Human neuropathology also has shown that striosomes and matrix have differential vulnerability patterns in several striatal neurodegenerative diseases. Postsynaptic density protein 95 (PSD-95), also known as DLG4, is a major scaffolding protein in the postsynaptic densities of dendritic spines. PSD-95 is now known to negatively regulate not only N-methyl-D-aspartate glutamate signaling, but also dopamine D1 signals at sites of postsynaptic transmission. Accordingly, a neuroprotective role for PSD-95 against dopamine D1 receptor (D1R)-mediated neurotoxicity in striatal neurodegeneration also has been suggested. Here, we used a highly sensitive immunohistochemistry technique to show that in the human neostriatum, PSD-95 is differentially concentrated in the striosome and matrix compartments, with a higher density of PSD-95 labeling in the matrix compartment than in the striosomes. This compartment-specific distribution of PSD-95 was strikingly complementary to that of D1R. In addition to the possible involvement of PSD-95-mediated synaptic function in compartment-specific dopamine signals, we suggest that the striosomes might be more susceptible to D1R-mediated neurotoxicity than the matrix compartment. This notion may provide new insight into the compartment-specific vulnerability of MSNs in striatal neurodegeneration.